Imperfect competition in a network industry: The case of the European rail freight market. (August 2017) - Laroche, Florent; Sys, Christa; Vanelslander, Thierry; Van de Voorde, Eddy
Abstract: Purpose: This paper opts for a time varying approach to measure the competition on the European rail freight sector according to two questions: what is the current level of competition and how is this expected to evolve in the long run? Approach: A firm-level dynamic panel estimates the persistence of profit in the European rail freight sector. Main findings: The persistence of profits shows a high degree of competition in the short run but imperfect in the long run due to the existence of barriers on the market. Secondly, the ratio between capital and labour cost is calculated. It indicates moderate economies of scale. Originality: Knowledge about this new market and the dynamics are limited in the academic literature. The research is relevant for the policy makers to monitor the rail freight market and to harmonise the practices between network managers to improve the European single market. Highlights: The analysis reveals positive signs of increasing competition. Operators are developing strategies of differentiation and new business models. We observed an increase in the number of newcomers after European liberalisation. There are still barriers on the market caused by imperfections in the single market. Current databases should be updated to include data on newcomers.